Assessing nesting status of green turtles, Chelonia Mydas in Perak, Malaysia - Mohd Salleh, Sarahaizad; Mohd Sah, Shahrul Anuar; Khan Chowdhury, Ahmed Jalal (Penerbit Universiti Sains Malaysia, 2018)
The nesting of green turtle (Chelonia mydas) was monitored from 1998 untill 2013 along the beaches of Pasir Panjang, Segari, Perak. The objective of the study is to assess the nesting status of green turtles in Perak, Peninsular Malaysia in terms of total nests,eggs, survival hatchings, and density of visitors. A total number of green turtle nests foundfor 16 years were 1,019 nests and varied from 10 to 220 nests per year. Meanwhile, the sum of eggs collected for 16 years were 107,820 eggs, and varied from 553 to 20,881 eggs per year. The temporal pattern of nesting indicates year-round nesting in Perak in most years within the 16 years period. The peak season of nesting was estimated to occur between May and June. Survival hatchlings varied from 23.33% (2,071 hatchlings) to 55.03% (5,018 hatchlings) from 1998 to 2013. The density of visitors was not uniformly distributed among the years, and shows a sign of decline especially from 2006 onwards. This publication provides basic knowledge of green turtle nesting population in Perak, and would be helpful in upgrading the conservation program in Malaysia. In future, we hope 1) for an increase in manpower to obtain accurate nesting records along the nesting beaches during nocturnal survey and, 2) to include the breeding biology data such as nest placement, emergence hour, and morphological characteristics of green turtle.